2020
DOI: 10.1515/jpem-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status is related to severity at onset of diabetes and worse glycemic control

Abstract: ObjectivesOur aim is to evaluate whether 25-hydroxyvitamin D at onset of type 1 diabetes mellitus (T1DM) would influence analytical variables of worse prognosis of the disease at the beginning and after one year of development.MethodsA retrospective study of pediatric patients (0–14 years) diagnosed with T1DM with initial measurements of 25-hydroxyvitamin D was performed at Son Espases Hospital, between March 2012 and April 2019 (n=67).ResultsVitamin D insufficiency was related to age, glycosylated hemoglobin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A summary of the selection process for the studies is presented in Fig. 1 Descriptions of included studies Out of the 45 studies, 19 had cross-sectional designs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], 23 were case-control studies , 2 had baseline cross-sectional data from a longitudinal study [64,65] and one was based on the baseline data of a cohort study [66]. The reported data also included 6,995 participants, mostly aged ≤ 18 years old, of which 2,436 were children/adolescents with T1D as well as vitamin D de ciency (sample size n=13~1,426).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the selection process for the studies is presented in Fig. 1 Descriptions of included studies Out of the 45 studies, 19 had cross-sectional designs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], 23 were case-control studies , 2 had baseline cross-sectional data from a longitudinal study [64,65] and one was based on the baseline data of a cohort study [66]. The reported data also included 6,995 participants, mostly aged ≤ 18 years old, of which 2,436 were children/adolescents with T1D as well as vitamin D de ciency (sample size n=13~1,426).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the recommended NOS and AHRQ criteria, only studies of acceptable quality were included in the present meta-analysis; eight studies received 9 stars [51,53,[56][57][58]62,63,66], ten studies received 8 stars [43,[48][49][50]52,54,55,[59][60][61], ve studies received 7 stars [42,[44][45][46][47] and one study received 6 stars [41]. When using the quality assessment criteria from the AHRQ, three studies received a score of 11 [24,29,65], ten received a score of 10 [22,25,28,29,31,33,34,36,39,40], three received a score of 9 [23,32,35], one received a score of 8 [27], one received a score of 7 [37] and two received a score of 5 [26,38], the quality assessment are shown in Appendix S2. Therefore, no article from the meta-analysis was excluded for quality reasons.…”
Section: Resultsmentioning
confidence: 99%
“… 31 This was consistent with other reports in which improvements in glycemic control measured by HbA1c levels were documented but without statistical significance. 23 , 24 , 32 In a systematic meta-analysis review conducted in 2022, Nascimento et al evaluated the effect of vitamin D supplementation on HbA1c levels and reported a significant improvement in glycemic control in 50% of the analyzed studies. 33 However, there is yet to be consistent evidence on the effect of vitamin D supplementation on the glycemic control of children/adolescents with T1DM, as other studies have shown that vitamin D supplements fail to improve glycemic control.…”
Section: Discussionmentioning
confidence: 99%